Fitinfluencers and their Impact on Body Perception in Spanish Young Adults: Possible Predisposing Factor in Male Vigorexia - Fanjul Peyró, Carlos; González Oñate, Cristina (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
The article presents an investigation carried out with the survey methodology where 1753 Spanish boys, between 17 and 24 years old and followers of fitinfluencers, respond to questions about how this following influences their perception and physical evaluation. Some of the conclusions point to the fact that this viewing influences the distortion of their physical evaluation. For them, fitinfluencers have a ‘desirable’ muscle definition and are a reference that affects them in varying their exercise routines (80%) and diet (60%). They consider that this ‘ideal’ body can be achieved by following the precepts that the fitinfluencers show them.